The Lesotho General Certificate of Secondary Education (2013): teachers' readiness for implementation - Letsie, Johson Mapoho (University of the Free State, 2019)
This study sought to explore teachers’ perceptions of their readiness to implement the Lesotho General Certificate of Secondary Education (LGCSE) which was introduced in 2013. The LGCSE was adopted as a result of critique against the Cambridge Overseas School Certificate (COSC), and was perceived as more aligned with the needs of the country and her people. Couched in a constructivist paradigm, this study was premised on the assumption that individuals create meaning from their interactions in their lives and the experiences they gain from work. In alignment with a qualitative methodology, data was generated through a document analysis, focus group discussions and semi-structured interviews. In this study I undertook a document analysis of Implementing the Curriculum with Cambridge: A Guide to School Leaders (undated) and the Curriculum and Assessment Policy (2009) (CAP). The analysis was used to highlight the differences between the COSC and the LGCSE curricula, and in particular, to indicate the similarties and differences between seleted syllabi. The research participants were purposively selected based on their experience in teaching towards both the COSC and the LGCSE. At two urban schools in Maseru city, two focus groups discussions were held with six participants from each school, and six semi-structured interviews were conducted, three at each school. The data generated through the focus group discussions was analysed by means of a constant comparison analysis. The findings revealed that the participants are aware of the differences between COSC and LGCSE, and they perceive the LGCSE as more accommodative in terms of the differentiation of learners’ ability in Mathematics and Physical science. In addition, they perceive the LGCSE curriculum as more relevant to address the needs of the Basotho. However, the one-day workshop was regarded as insufficient to adequately prepare the teachers for the transition from the COSC curriculum to the LGCSE curriculum. These findings were in general corroborated by the data generated from the semi-structured interviews. The workshops held to train teachers were perceived as just a space for information dissemination, rather than an opportunity to gain information on the strategies and approaches of teaching the new syllabi content. In particular, the findings revealed that the training was insufficient in assisting teachers with the selection of learners to study the respective core and the extended syllabi. In addition, they also struggled with the content of the new topics as they were not dealt with in detail during the one-day workshop. The findings indicated that the one-day training workshop did not enable the teachers to frame their teaching within an integrated approach as required by CAP. In general, the research participants indicated that the Ministry of Education and Training (MOET) did not sufficiently prepare them for the implementation of the LGCSE curriculum. The study concludes by suggesting that training workshops should be held on a regular basis with a focus on specific aspects of the curriculum in more detail, and also on CAP as a policy framework intended to guide education reform in Lesotho. It is also suggested that MOET contributes towards creating spaces for teachers to colloratively work together on the implementation of the LGSCE curriculum
Dissertation (M.Ed. (School of Education Studies))--University of the Free State, 2019
Keywords: Teacher perception; Lesotho General Certificate of Secondary Education; Cambridge Overseas School Certificate; Constructivist paradigm; Qualitative research